Maturity of processes in smes: validation of scales when implementing project-based learning - Carballo-Mendívil, Blanca; Arellano-González, Alejandro; Ríos-Vázquez, Nidia Josefina (Journal of Management and Business Education, 2019)
This paper presents the design and validation of scales that can be used in project-based learning (PBL) when a small service company is studied, particularly the maturity of their business processes. The scales were designed based on an organization model with a systems approach. To validate the scales, data were collected by students through rubrics, after participating in a semester-long PBL process developed for a university course. The reliability was determined and the factorial structure examined by an Exploratory Factor Analysis. Nine instruments were obtained as a final result of the project, in scoring rubric format that expresses four levels of maturity, from 16 attributes that comprehensively evaluate a process’ maturity. The analysis revealed that the greatest scope for improvement in small businesses is in managing infrastructure and environment. The value of the proposed scales is because they offer a holistic manner to analyze the organizational processes, with a maturity approach. This is because organizations, as well as living beings, mature in different stages, and therefore must be treated accordingly. This study also laid out a methodology to organize a project-based pedagogy. This methodology can be incorporated into a class plan and complement the theoretical and empirical knowledge necessary for the student to move from theory to practice naturally, while developing skills and attitudes required by a consultant or business analyst with teacher orientation.